Introducing race and gender into economics - Bartlett, Robin L. (Routledge, 1997)
"Introducing race and gender into economics is the first book to provide a detailed model of how issues of race and gender can be integrated into the teaching of an introductory economics course. The book's innovative structure mirrors a typical introductory course and suggests alternative examples and approaches which have a race and/or gender perspective."--Jacket